Strukturalne promjene motorickih sposobnosti kod mladih plivaca, reprezentativaca Bosne i Hercegovine, uvjetovanih trenažnim procesom - Dedovic, D.; Popo, A.; Cemalovic, C. (Sportski Logos, 2013)
The main objective of this study was to determine the structural changes of motor skills in young swimmers representatives of Bosnia and Herzegovina. The research was conducted on a sample of ten (10) swimmers, government representatives of Bosnia and Herzegovina in swimming, participants BiH state championship in swimming. For final processing to take all the results of the respondents who participated in the control study, the competition and the diagnostic test after the national championships. For the assessment of motor skills applied 16 variables covering latent space motoric capabilities. To determine the structural changes in factor analysis with orthoblique set. In the area of motor skills separately obtained four factors, titled: timing when swimming, fixation around the center of mass, the active role of the lower extremities and optimization of movement through the water. Correlation factors are defined in such a way that some extremely high values. Between the first and the third factor is extremely high bond 0.61, which means that these two factors strongly associated. The same applies to the first and fourth, because the correlation between these factors 0.67. This information is understandable because it is an optimization of motion in the water, therefore, strictly specifically in swimming. Studies of this type are extremely rare in our country, and are very important for the quality selection of swimmers and adequately programmed training process.